2021
DOI: 10.15294/biosaintifika.v13i3.30527
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Proximate Composition of Local Corn Cultivar from Kisar Island, Southwest Maluku Regency

Abstract: As a staple food, which consumed by many peoples in almost all places world wide, corn (Zea mays L.) has become very important. As well as in Indonesia, especially in Kisar Island, Southwest Maluku regency, corn already be the one of the most important food crops. The purpose of this study was to determine proximate content of local corn kernels from Kisar Island Maluku. Proximate analysis included content of water, fat, protein, ash, crude fiber, total carbohydrate and total sugar. Data collected are presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
2
5
0
1
Order By: Relevance
“…This is in line with the results of the research by Nikolic (2021) which showed that the results of measuring the ash content of the baby corn variety ZP 366 were 1.38% and those of the ZP 611k variety were 1.40% [41]. Feed corn from South Maluku has been measured by a study conducted by Sinay (2021) [42]. The varieties whose ash content were measured included merah delima tongkol cokelat, merah delima tongkol putih, merah darah, pulut, kuning genjah, kuning dalam and putih.…”
Section: Ash Content Of Sweet Cornsupporting
confidence: 87%
See 2 more Smart Citations
“…This is in line with the results of the research by Nikolic (2021) which showed that the results of measuring the ash content of the baby corn variety ZP 366 were 1.38% and those of the ZP 611k variety were 1.40% [41]. Feed corn from South Maluku has been measured by a study conducted by Sinay (2021) [42]. The varieties whose ash content were measured included merah delima tongkol cokelat, merah delima tongkol putih, merah darah, pulut, kuning genjah, kuning dalam and putih.…”
Section: Ash Content Of Sweet Cornsupporting
confidence: 87%
“…The varieties whose ash content were measured included merah delima tongkol cokelat, merah delima tongkol putih, merah darah, pulut, kuning genjah, kuning dalam and putih. The ash content values of the measurement results for each of these varieties respectively were: 1.57%, 2.04%, 1.13%, 1.69%, 1.23%, 1.39% and 1.43% [42]. According to the Indonesian National Standarda/SNI (1998) regarding feed corn, the maximum ash content in corn is 2% [43].…”
Section: Ash Content Of Sweet Cornmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is due to the superiority of germination resulting from soaking the seeds in licorice root extract, as it contains sugars, which in turn help to reduce or limit cold damage as a result of the increase of dissolved solids in plant cells, which increases the plant's resistance to these damages [24]. As for the treatment of soaking with potassium nitrate, it can improve the ability of seeds to germinate through the synthesis and transport of carbohydrates and increase the sugar content, in addition to that it acts as a temporary storage of nitrogen and potassium, which can be used later, and this is consistent with what was found by [25]relating to soaking corn seeds in potassium nitrate. It is believed that the role of the two factors in increasing the percentage of germination in the cold test is due to their stimulating role in seed germination and the destruction of the endosperm through the entry of water and oxygen into the seeds, the transfer of nutrients to the embryo, and faster germination.…”
Section: Germination Percentage At the Accelerating Age Testsupporting
confidence: 80%
“…Corn is a carbohydrate-producing plant that occupies the second position in Indonesia after rice [1]. From the data obtained in 2021, the amount of corn production in Indonesia reaches around 15.79 million tons, proving that corn production in Indonesia is very large [2].…”
Section: Introductionmentioning
confidence: 99%